68Ga-DOTAGA-IAC PET/CT for Imaging Metastatic and Recurrent Adrenocortical Carcinoma: A Case Series. (February 2023) - Pandey, Somit; Walia, Rama; Kumar, Rajender; Chopra, Sejal; Rana, Nivedita; Chatterjee, Debajyoti; Satz, Stanley; Mittal, Bhagwant Rai; Shukla, Jaya
Abstract: Adrenocortical carcinoma (ACC) is a rare malignancy with a prevalence of 1 to 2 cases/million/year. The diagnosis depends upon endocrine workup followed by imaging with CT, MRI, and 18 F-FDG PET/CT. The treatment includes surgical resection, debulking surgery, chemotherapy, and radiotherapy. However, patients do not respond well to any of the available therapies. We present noninvasive imaging of histopathology-proven ACC patients using 68 Ga-DOTAGA-IAC PET/CT, specific for integrin αv β3 . 68 Ga-DOTAGA-IAC PET/CT 45 minutes after IV injection showed a decent tumor-to-background ratio and could be used as a promising radiotracer for metastatic and recurrent ACC.